Kontribusi Gerakan Pemuda Ansor dalam Pengembangan Pendidikan Islam di Kabupaten Kepahiang - Muhamad Yamin; Nelson Nelson; Bariyanto Bariyanto (Institut Agama Islam Negeri Bengkulu, 2020)
This study aimed at finding out a depiction of GP Ansor’s work programs in Kepahiang Regency, especially in providing Islamic education and knowledge in the midst of society. This study used a quality approach as aligned with the purpose of this study, and the data collection techniques were observation, interviews and documentation. After the data were collected, the data were carefully selected according to those of which could answer the formulated research objective. Thus, the following conclusion could be drawn: First, Islamic education was implemented by GP Ansor of Kepahiang regency through Islamic teachings of Majelis Dzikir and Sholawat Rijalul Ansor, Safari Ramadhan, Tabligh Akbar, Halal Bi Halal, khitanan massal, the commemoration of Islamic great days (PHBI), the coaching of Aswaja, and the coaching of young Da'i in Kepahiang regency. Second, the supporting factors included adequate organizational structures from district to village levels which had the same programs as the priority, plus semi-autonomous organizational structures, adequate facilities, and qualified human resources (HR). Meanwhile, there were two factors that inhibited GP Ansor in carrying out Islamic education programs in Kepahiang Regency, namely the limited funds and a matter of time allocation for administrators and members because they had diverse daily routines and activities in carrying out their respective jobs.